Mesenchymal Stromal Cells, a New Player in Reducing Complications From Liver Transplantation? - Owen, Andrew; Newsome, Philip N. (Frontiers in Immunology, 2020)
In response to the global burden of liver disease there has been a commensurate increase in the demand for liver transplantation. However, due to a paucity of donor organs many centers have moved toward the routine use of marginal allografts, which can be associated with a greater risk of complications and poorer clinical outcomes. Mesenchymal stromal cells (MSC) are a multi-potent progenitor cell population that have been utilized to modulate aberrant immune responses in acute and chronic inflammatory conditions. MSC exert an immunomodulatory effect on innate and adaptive immune systems through the release of both paracrine soluble factors and extracellular vesicles. Through these routes MSC can switch the regulatory function of the immune system through effects on macrophages and T regulatory cells enabling a switch of phenotype from injury to restoration. A key benefit seems to be their ability to tailor their response to the inflammatory environment without compromising the host ability to fight infection. With over 200 clinical trials registered to examine MSC therapy in liver disease and an increasing number of trials of MSC therapy in solid organ transplant recipients, there is increasing consideration for their use in liver transplantation. In this review we critically appraise the potential role of MSC therapy in the context of liver transplantation, including their ability to modulate reperfusion injury, their role in the reduction of medium term complications in the biliary tree and their potential to enhance tolerance in transplanted organs.